Optically bright p-excitons indicating strong Coulomb coupling in transition-metal dichalcogenides. (3rd August 2015) - Stroucken, T; Koch, S W
Abstract: It is shown that the strong Coulomb coupling in intrinsic suspended semiconducting transition metal dichalcogenides can exceed the critical value needed for an excitonic ground state. The dipole-allowed optical excitations then correspond to intra-excitonic transitions such that the optically bright excitonic transitions near the Dirac points have a p -like symmetry, whereas the s -like states are dipole forbidden. The large intrinsic coupling strength seems to be a generic property of the semiconducting transition metal dichalcogenides and strong Coulomb-coupling signatures in the form of the optical selection rules can be observed even in samples grown on typical substrates like SiO2 . For the examples of WS2 and WSe2, excellent agreement of the computed excitonic resonance energies with recent experiments is demonstrated.